Effect of External Pressure on Skin Blood Flow at Lower Limb in Different Postures (Journal of Fiber Bioengineering and Informatics, 2018)
The influence of garment pressure on human physiological activities has attracted researchers from many areas. In this study, to investigate the effect of external pressure on skin blood flow (SBF) at lower limb in different postures, external pressure was exerted on lower limb in supine and sitting postures using sphygmomanometer. Five undergraduate male students volunteered to participate in the study. An alternating pressure loading protocol between non-pressure and pressure of 20mmHg or 40mmHg was employed. The SBF undergoing pressure was observed with Laser Doppler Flowmeter. It was found that the SBF increased under low pressure and began to decrease as the pressure exceeded a certain level (around 35mmHg). It was speculated that the change in SBF due to external pressure was the result of balance between the neural effect and mechanical effect. The blood pressure in supine posture was lower than that in sitting posture, thus the blood pressure in metarterioles was lower in supine posture and thereby the SBF began to decrease under lower pressure in supine posture than that in the sitting posture. In the case of microcirculation, high pressure can be an obstacle, particularly in supine posture. These findings will be helpful in the design and application of tight-fit garments.
Keywords: Skin blood flow; external pressure; laser doppler flowmeter; posture change; lower limb; supine